Assessment of proposed lateral resistance system used with framed structures - Fateh, Amir (2016)
Vibration due to dynamic loadings can cause excessive oscillations in the building, which may lead to structural failure. Since Safety assurance, the functionality of structure and economic design are the most important concerns of structural engineers, many studies have been conducted to improve aforementioned issues. The variable stiffness concept, which is one of the vibration energy dissipation techniques, has been implemented in the different structures and mechanical devices to provide system stability and mitigate the undesirable damages induced by vibration effects. Numerous studies have been conducted, specifically in structural engineering, to develop and evaluate the dynamic performance of energy dissipation systems based on the variable stiffness concept, such as active, semi-active, and passive variable stiffness methods. Whereas the, most of the variable stiffness systems are operated using high-tech signal processors, controllers, and external electrical supply.Additionally, the aforesaid systems are highly dependent on controller, energy resources and required repetitive maintenance. Therefore, developing a realtime system without any dependency on abovementioned conditions are highly required.This study develops two types of adaptive variable stiffness devices: variable stiffness bracing (VSB) and nonlinear spring conical bracing (NCSB). These devices are applicable as lateral resistant and vibration absorbers in a framed building subjected to dynamic loadings. The research methodology in the current study can be categorized into two general sections include of numerical simulation and experimental test.Configurations of devices and mathematical models are established. The specific finite element algorithms are developed and implemented in the finite element program code for the nonlinear analysis of RC framed buildings. Various analyses, including pushover and time history, are conducted on different framed building models equipped with both the proposed devices. The developed finite element program and efficiencies of the offered devices in terms of structural response are evaluated. The possibilities of plastic hinge formations in structural components are also identified through nonlinear dynamic analysis. Results obtained from numerical analyses confirm the effectiveness of the developed devices in maintaining the structural stability of the framed buildings. Experimental section is divided into two main sections consisted of the cyclic test and direct compression test.Cyclic test conducted based on displacement control approach in steel and RC frames. Four steel and three RC frame specimens subjected to cyclic displacement history on their top nodes. These models included of the frame without and with attached VSB and NCSB devices and conventional X-braced frames. The efficiency of VSB and NCSB applications in frames compared with bare and brace frames in terms of ductility characteristics, maximum capacity,stiffness and etc. Based on parametric time history analysis on the single degree of freedom models, the application of VSB and NCSB caused to decrease the maximum displacement up to 60% and 33% respectively compare to bare model. These devices reduced the maximum velocity and acceleration values. Additionally,results from parametric 3D pushover analysis show the noticeable increase in terms of failure capacity up to 43% and 15% for model furnished by VSB and NCSB devices. Generally, the results from the parametric study reveal that the geometry specification of devices plays an important role in the structural response and plastic hinge formation in structural elements. Moreover, results from 3D time history analysis on model equipped with VSB and NCSB devices illustrate the maximum value of shear and moment forces as well as the number of plastic hinge formations in structural components reduced dramatically.Aside from the numerical analysis, an experimental test is conducted to assess the functionality and performance of the developed adaptive systems in different structural types that consist of steel and RC frames subjected to cyclic dynamic test equipped with NCSB and VSB devices. The ductility behavior,overall stiffness and failure mechanism enhanced in both RC and steel frames compared with the bare frame. In brief, the experimental results show a noticeable improvement in the performance of RC and steel frames equipped with the abovementioned devices.